2016
DOI: 10.1210/jc.2016-1856
|View full text |Cite
|
Sign up to set email alerts
|

One-Hour Postload Hyperglycemia Confers Higher Risk of Hepatic Steatosis to HbA1c-Defined Prediabetic Subjects

Abstract: These data suggest that a value of 1-hour postload glucose ≥155 mg/dL may be helpful to identify a subset of individuals within HbA1c-defined glycemic categories at higher risk of hepatic steatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 38 publications
(44 reference statements)
2
33
0
1
Order By: Relevance
“…The design of the CATAMERI study has been previously reported [14,[25][26][27]. The study cohorts include 2055 participants used to estimate the linear relationship between fasting plasma glucose and HbA1c in the study population to calculate the predicted HbA1c value, and 1120 individuals in whom hepatic steatosis was assessed by ultrasonography.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The design of the CATAMERI study has been previously reported [14,[25][26][27]. The study cohorts include 2055 participants used to estimate the linear relationship between fasting plasma glucose and HbA1c in the study population to calculate the predicted HbA1c value, and 1120 individuals in whom hepatic steatosis was assessed by ultrasonography.…”
Section: Methodsmentioning
confidence: 99%
“…A growing body of evidence suggests that NAFLD is strongly associated not only with impaired glucose metabolism and obesity [5][6][7] but also with an increased risk to develop diabetes mellitus [8][9][10], and an independent association between NAFLD and glycated hemoglobin (HbA1c) levels has been reported in several studies [11][12][13][14]. HbA1c is the gold standard for evaluating glucose control in patients affected by diabetes mellitus and for monitoring the efficacy of therapies [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed 1723 individuals consecutively recruited at the Department of Systems Medicine of the University of Rome-Tor Vergata and at the Department of Medical and Surgical Sciences of the University ''Magna Graecia'' of Catanzaro as previously described [30,[32][33][34][35][36][37][38].…”
Section: Methodsmentioning
confidence: 99%
“…Evidence has accrued suggesting that subjects with a 1-h plasma glucose concentration during an oral glucose tolerance test (OGTT) [155 mg/dl (8.6 mmol/l) are at increased risk of type 2 diabetes among those who have NGT [28][29][30][31]. Remarkably, subjects with 1-h postchallenge plasma glucose [155 mg/dl are characterized by a cluster of cardio-metabolic abnormalities such as insulin resistance [32], pro-atherogenic lipid profile [33], hepatic steatosis [34], carotid atherosclerosis [35], vascular stiffness [36], and left ventricular hypertrophy [37], and cardiac autonomic imbalance [38] which in turn have been inked to increased blood viscosity [1,3,[7][8][9][10][11]. The degree to which 1-h post-load plasma glucose [155 mg/dl is associated with blood viscosity remains unsettled.…”
Section: Introductionmentioning
confidence: 99%